2010
DOI: 10.1021/es101009x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in European Background Air Reflect Reductions in Primary Emissions of PCBs and PBDEs

Abstract: Synthesis of Carbamates by Direct C-H Bond Activation of Formamides. -A wide range of β-ketoesters and 2-ketosubstituted phenols are effectively transformed into the corresponding carbamates in the reaction with formamides. The use of 6 equiv. of TBHP is crucial. Low yield of the product is observed when a cyclic diketone (IV) is applied. The method is extended to the preparation of a carbaryl insecticide derivative (XII). -(CHANG*, F.-R.; et al.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 38 publications
7
79
0
Order By: Relevance
“…Due to this data variability, we cannot confirm a decline in PBDE concentrations after their regulation. Recent studies of temporal trends of PBDEs in different matrixes also show no clear trends Hermanson et al, 2010;Kohler et al, 2008;Meyer et al, 2012;Schuster et al, 2010Schuster et al, , 2011. These various archives and long-term measurements were influenced by factors such as diverse sources or post-depositional effects that may explain some of the differences observed between the results.…”
Section: Temporal Variationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Due to this data variability, we cannot confirm a decline in PBDE concentrations after their regulation. Recent studies of temporal trends of PBDEs in different matrixes also show no clear trends Hermanson et al, 2010;Kohler et al, 2008;Meyer et al, 2012;Schuster et al, 2010Schuster et al, , 2011. These various archives and long-term measurements were influenced by factors such as diverse sources or post-depositional effects that may explain some of the differences observed between the results.…”
Section: Temporal Variationsmentioning
confidence: 87%
“…To the best of our knowledge, researchers have only studied ice or snow cores as a natural archive for airborne PFASs or PBDEs in the Arctic (Hermanson et al, 2010;Meyer et al, 2012;Young et al, 2007). Other types of natural archives or sampling techniques that record temporal trends of PBDEs include long-term passive sampling (Schuster et al, 2010), vegetation and soil samples (Hassanin et al, 2005;Schuster et al, 2011), and lake sediment cores Kohler et al, 2008). Peat bogs, human serum, sediment cores and associated biota record PFASs back to the 1950s (Ahrens et al, 2009;Dreyer et al, 2012;Sturm and Ahrens, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that a direct comparison of data listed in Table 1 is difficult as the data reflect different sum of congeners and time periods. For example, the PCB levels in Europe (Schuster et al, 2010) and USA (Sun et al, 2006) has reduced drastically in the recent years. Still, the concentrations from this study are much higher when compared to the levels reported in Italy, Germany, Singapore and Korea.…”
Section: Atmospheric Levels Of Pcbsmentioning
confidence: 99%
“…Like the other parts of the world, the declining trend has been found in other regions. At the background sites of Europe, Schuster et al (2010) considered that PBDE concentrations of air declined by 50% from 2000 to 2008. Compared with the previous study of Wang et al (2005), Möller et al (2011) found a significant decline along the same transect from the East China Sea to the high Arctic.…”
Section: Comparison With Previous Research In East Asiamentioning
confidence: 99%
“…As for PBDEs, changes in the emission amount can be directly observed with the aid of PAS, though comparing the atmospheric PBDE concentrations at different periods in the same region. For instance, a recent study (Schuster et al, 2010) reported a decline in PBDE levels during [2000][2001][2002][2003][2004][2005][2006][2007][2008] at background sites in the UK and Norway.…”
Section: Introductionmentioning
confidence: 99%